Perceived and lived space in the modern city. A case study for Akadimia Platonos neighborhood, Athens, Greece - Georgios D. LAMPROPOULOS; Yorgos N. PHOTIS; Maria PIGAKI (European Journal of Geography)
The main objective of this paper is to perform a spatial analysis of everyday life experiences by enriching a socio-spatial approach within the boundaries of Akadimia Platonos neighborhood, in the city of Athens. It investigates the convergences and divergences that are observed between two different manifestations of space, as they have been approached through Henri Lefebvre’s social theory of space, the perceived space and the lived space. Mainly, the designed-geometric space, enhanced with all those relationships programmed for social reproduction, creates an experience for its users. Does this lived experience, that is expected to be experienced, actually correspond to reality? In the methodological framework proposed, perceived space (as spatial practices) is examined through the space syntax analysis of the study area, while lived space (as representational spaces) is accessed through questionnaire interviews, which examine the space perception of residents, workers, visitors, passers-by, using it.